Solid-State Single-Port Series Damping Device for Power Converters in DC Microgrid Systems - Wang, Ke-Wei; Zhang, Xin; Chung, Henry Shu-Hung (IEEE transactions on power electronics, 2019)
In dc microgrid systems, power converters with input filters sometimes encounter unwanted input voltage and current oscillations, due to interactions among the bus impedance, filters, and converters. This paper presents a solid-state single-port series damper (" S 3 damper") that can deal with such oscillations. The damper, which is connected in series between the input filter and the converter, is realized by operating a transistor as an ac resistor. It lowers the quality factor of the filter and thus increases the damping effect on the interaction between the filter and the converter. It also increases the input impedance of the filter to avoid voltage and current oscillation between the filter and the bus. In addition, the transistor is regulated at a low dropout voltage to reduce power dissipation. The control mechanism is autonomous. Furthermore, the proposed damper does not require any power capacitor or inductor, favoring high compactness and reliability. Modeling, design, and comprehensive analysis of the S 3 damper will be provided. A prototype damper for a commercially available 100 W dc-dc converter operated on a 48 V bus has been built and evaluated.